External contamination of commercial containers by antineoplastic agents: a literature review - Hilliquin, Delphine (Eur J Hosp Pharm, 2020)
The aim of this study was to review the literature regarding the external contamination of commercial vials by antineoplastic drugs. A PubMed and CINAHL searches from 1 January 1990 to 1 May 2018 was performed with the terms: « antineoplastic agents », « environmental monitoring », « drug packaging », « vials » and « contamination ». Articles that presented results on the external contamination of commercial vials were included. Twenty-four articles were identified from 11 countries. A total of 4248 vials were sampled from 28 manufacturers. Traces were found on 56% (2379/4248) of vials. A maximum of 150 000 ng was measured on a glass vial of fluorouracil. This literature review showed that the exterior of the majority of commercial antineoplastic vials was contaminated. Manufacturers should limit this contamination. Centres are also encouraged to clean the vials on receipt. Personal protection equipment should be worn at all steps of the drug-use process.